Pengaruh Metode Mind Mapping terhadap Kemampuan Memahami Teori Seni Rupa Siswa di Kelas VIII SMP Swasta Imelda Medan - Fany Chairina; Mesra Mesra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of the mind mapping learning method on students’ ability to understand visual art theory among eighth-grade students at SMP Swasta Imelda Medan in the 2025/2026 academic year. This research used an experimental method with a pretest–posttest control group design. The population in this study consisted of all eighth-grade students of SMP Swasta Imelda Medan, with two classes selected as samples: an experimental class and a control class. The data collection technique used a test to measure students’ understanding of visual art theory, which was administered before and after the treatment. Data analysis was conducted through normality testing, homogeneity testing, and hypothesis testing using the t-test. The results of the study showed that there was an effect of the use of the mind mapping method on students’ ability to understand visual art theory. The average posttest score in the experimental class was higher than that of the control class. Thus, the mind mapping method has been proven to improve students’ ability to understand visual art theory concepts in a more structured and systematic manner.